Oncolytic Adenovirus-Loaded Menstrual Blood Stem Cells Overcome the Blockade of Viral Activity Exerted by Ovarian Cancer Ascites - Alfano, Ana Laura (2017)
Patients with ovarian cancer present peritoneal ascites at recurrence as a marker of disseminated disease and dismal prognosis. Oncolytic immunotherapy is an emerging approach for the treatment of disseminated cancer. In the present work, we constructed a novel oncolytic adenovirus, AR2011, to target malignant ovarian tumors. AR2011 exhibited a clear lytic effect in vitro in human ovarian cancer cell lines and malignant cells obtained from ascitic fluids (AFs) of patients with ovarian cancer. AR2011 activity was neutralized by antibodies present in 31 samples of patient-derived AFs. However, this blockade was overridden by preloading menstrual blood stem cells (MenSCs) with AR2011 (MenSC-AR), since AFs exerted no in vitro inhibitory effect on viral lytic activity under these conditions. Moreover, soluble factors present in AFs act as MenSC chemoattractants. MenSC-AR treatment of nude mice carrying established peritoneal carcinomatosis following administration of human ovarian cancer cells was able to inhibit tumor growth at levels similar to those observed with AR2011 alone. This study demonstrates that MenSCs can be used to override the blockade that AFs exert on viral oncolytic effects.